Implementing Statewide Newborn Screening for New Disorders: U.S. Program Experiences - Yvonne Kellar-Guenther; Sarah McKasson; Kshea Hale; Sikha Singh; Marci K. Sontag; Jelili Ojodu (MDPI AG, 2020)
Data were collected from 39 newborn screening (NBS) programs to provide insight into the time and factors required for implementing statewide screening for Pompe, Mucopolysaccharidosis type I (MPS I), adrenoleukodystrophy (ALD), and Spinal Muscular Atrophy (SMA). Newborn screening program readiness to screen statewide for a condition was assessed using four phases: (1) approval to screen; (2) laboratory, follow-up, and information technology capabilities; (3) education; and (4) implementation of statewide newborn screening. Seventeen states (43.6%) reached statewide implementation for at least one new disorder. Those states reported that it took 28 months to implement statewide screening for Pompe and MPS I, 30.5 months for ALD, and 20 months for SMA. Using survival curve analysis to account for states still in progress, the estimated median time to statewide screening increased to 75 months for Pompe and 66 months for MPS I. When looking at how long each readiness component took to complete, laboratory readiness was one of the lengthier processes, taking about 39 months. Collaboration with other NBS programs and hiring were the most frequently mentioned facilitators to implementing newborn screening. Staffing or inability to hire both laboratory and follow-up staff was the most frequently mentioned barrier.